Seasonal Variation in Transcriptomic Profiling of Tetrastigma hemsleyanum Fully Developed Tuberous Roots Enriches Candidate Genes in Essential Metabolic Pathways and Phytohormone Signaling - Xiang, Qianqian; Hu, Siyuan; Ligaba-Osena, Ayalew; Yang, Jiayao; Tong, Fudan; Guo, Wanli (Frontiers in Plant Science, 2021)
Tetrastigma hemsleyanum Diels et Gilg. (Sanyeqing, SYQ) is a perennial climbing liana and endemic plant to southern China. Its tuberous roots (TRs) are used as traditional medicinal for treating some diseases such as high fever, pneumonia, asthma, hepatitis, and cancers with little or no cell-toxicity. However, the mechanisms of TR development, and accumulation of flavonoids and phenylpropanoids (FPs), which are the main components in SYQ fully developed (FD) TRs (FD-TRs), are not well understood. In this study, we performed transcriptome analysis of 12 FD-RT samples harvested in four seasons (Sp: spring; Su, summer; Au, autumn, and Wi, winter) using RNA-Seq. We obtained a total of 78.54 Gb raw data, and 65,578 unigenes after filtering and assembling. The unigenes were then annotated using six databases: NCBI-NR, Pfam, eggNOG, SwissProt, KEGG, and GO. The transcriptomic expression patterns showed closer relationships between Su and Au samples than Sp and Wi, and similar results were obtained in analysis of different expression genes (DEGs). The three gene groups significantly enriched by KEGG were FP biosynthesis, starch and sucrose metabolism, and phytohormone signaling, suggesting a seasonal variation in the level of each gene group in FD-RTs. Brassinosteroid signal factors appear to play a key role in modulating the growth of FD-RTs while most auxin signaling genes were mainly activated in Wi and Sp. Most genes of the starch biosynthesis and degradation, and cellulose degradation were activated in the Wi samples. As determined by high performance liquid chromatography (HPLC), the levels of most FPs increased from Sp to Au but decreased in Wi. The highest expression levels of some genes in the biosynthetic pathways were detected in Su and Au, which corroborates well with metabolite accumulation. Our findings provide the first comprehensive transcriptomic and biochemical data on seasonal variation in the composition of medically important metabolites in SYQ DF-TRs.